Quantitative quality of service for grid computing : applications for heterogeneity, large-scale distribution, and dynamic environments - Wang, Lizhe, 1974-; Chen, Jinjun; Jie, Wei (Hershey, PA : Information Science Reference, 2009)
'This book provides research into parallel & distributed computing, high performance computing, and Grid computing'--Provided by publisher
Includes bibliographical references (p. 451-484) and index
Keywords: Computational grids (Computer systems) -- Quality control; Parallel processing (Electronic computers); Electronic data processing -- Distributed processing; High performance computing